Cystic fibrosis – to take care of patients with standards - Cofta, Szczepan (Przewodnik Lekarza/Guide for GPs, 2010)
Cystic fibrosis (CF) is the most common autosomal recessive disorder in Caucasians. Even though CF is a multiorgan disaese, progressive lung destruction is the most common cause of morbidity and mortality. Recent advances in the diagnosis and treatment of CF, allow patients who were diagnosed as children to live to adulthood and new diagnoses in adults be made. It implicates a proposition of standards concerning medical and non-medical problems what should be carried by multi-specialistic team of medical staff.